Pelaksanaan Perencanaan Pembangunan Berkelanjutan Di Kawasan Industri (Studi pada Ngoro Industrial Park Di Kabupaten Mojokerto) - Agustin Harum Pratiwi (Jurnal Administrasi Publik, 2016)
Abstract: The Implementation of Sustainable Development Planning in Industrial Estate (Study on Ngoro Industrial Park in Mojokerto Regency). Ngoro Industrial Park industrial estate management is implemented by the industrial estate company PT Dharmala-Retire Servicement Engineering Industrial Estate Agency but since 2014 changed its name to PT. Kawasan Industri Intiland. NIP industrial estate located in the valley of Mount Penanggungan Village District of Ngoro Mojokerto regency East Java Province. NIP industrial estate development is planned in two phases, where the first phase of NIP industrial area began in 1991 with a land area of ​​215 hectares and the second phase was implemented in August 2010 with a land area of ​​225 hectares, bringing the total area of ​​the industrial area NIP ± 440 hectares. In the implementation of phase 2 that dlihat development of the concept of sustainable development must pay attention to three aspects of sustainable development of the social, economic, and environmental. and refers to the Regulation of the Minister of Industry of the Republic of Indonesia Number 35/M-IND/PER/3/2010 on technical guidelines for the industrial area, the implementation should consider five principles of the development of industrial areas, among others, the suitability of spatial plans Mojokerto, availability of infrastructure and facilities, eco-friendly, efficiency, and security and comfort sought. Keywords: Implementation, Sustainable Development, Industrial Estate   Abstrak: Pelaksanaan Perencanaan Pembangunan Berkelanjutan Di Kawasan Industri (Studi Pada Ngoro Industrial Park Di Kabupaten Mojokerto). Pengelolaan kawasan industri NIP dilaksanakan oleh perusahaan kawasan industri yakni PT Dharmala-Retire Servicement Engineering Agency Industrial Estate namun sejak tahun 2014 berganti nama menjadi PT. Kawasan Industri Intiland. Kawasan industri NIP terletak di lembah Gunung Penanggungan Desa Ngoro Kecamatan Ngoro Kabupaten Mojokerto Provinsi Jawa Timur. Pembangunan kawasan industri NIP direncanakan dalam 2 tahap, dimana tahap pertama kawasan industri NIP dimulai pada tahun 1991 dengan luas lahan 215 Ha dan tahap kedua dilaksanakan pada bulan agustus tahun 2010 dengan luas lahan 225 Ha sehingga total luas area kawasan industri NIP ± 440 Ha. Dalam pelaksanaan pembangunan tahap 2 yang dlihat dari konsep pembangunan berkelanjutan maka harus memperhatikan 3 aspek pembangunan berkelanjutan yakni aspek sosial, ekonomi, dan lingkungan. dan merujuk pada Peraturan Menteri Perindustrian Republik Indonesia Nomor 35/M-IND/PER/3/2010 tentang pedoman teknis kawasan industri maka dalam pelaksanaannya harus memperhatikan 5 prinsip pengembangan kawasan industri antara lain kesesuaian rencana tata ruang wilayah Kabupaten Mojokerto, ketersediaan prasarana dan sarana, ramah lingkungan, efisiensi, dan keamanan dan kenyamanan berusaha.   Kata kunci: Implementasi, Pembangunan Berkelanjutan, Kawasan Industri